The Creation of the Right of Real Servitude: Derivative and Original Method Based on the Kosovo and Some European Countries - Kastriote Vlahna; Hajredin Kuçi (Faculty of Law, Hasanuddin University, 2022)
Legal provisions define the right of servitude as a real right both in local legislation and in the legislation of European countries. Based on the local legislation, some shortcomings are encountered when it comes to the right of servitude, particularly the right of servitude in kind. An issue that will have to be addressed and compared with the legislation of other countries is the crime of the right of real servitude, based on the ways of creating this right. Based on the local legislation, it is emphasized that the right of real servitude can be created based on a legal title, the decision of a state body and based on the law. At the same time, no more detailed division is made to show which legal title belongs in which way, that of derivatives or original. In comparison, legislation of European countries such as Germany, Austria and France, as well as regional countries, it is emphasized that there are two ways for the crime of the right of real servitude. After the ways are mentioned, the separation of legal titles is done; such a thing should be defined in the legislation of Kosovo. Nevertheless, based on the provisions of the legislation in force, we note that where the legal titles for the creation of the right of real servitude are mentioned, there it is known that there are two ways of creating the right of real servitude that the derivative way and the original way of obtaining the right of real servitude, only that it would be more correct if they specified which legal title is considered a derivative title, which in our case is the contract and testament, and which would be considered an original title, which could be the decision of the state body such as that of the court or any administrative body.